Samuel Colman, 1780-1845 - Whidden, Margaret (The University of Edinburgh, 1986)
Because he lived in Bristol between the years 1816 and 1838, Samuel Colman is usually considered a 'Bristol School' artist. Although few biographical details are available about this provincial drawing master, the most important to emerge are those which clarify his religious affiliations and links. Again, while there is little evidence that Colman was closely connected with the other members of the Bristol school, it is clear that he had much in common with them as regards subject matter and sources, and that his work was known to other Bristol artists, and theirs to him. Therefore, while the purpose of this study of Samuel Colman has been to illuminate the work of an apparently very private artist, the result of the research has been to widen the 'picture' of Independency in pre-Victorian Bristol, while adding something to the definition of the 'school' of art which the city produced during that period.

Colman's connections with mainstream Dissent, through his membership of Castle Green and of Zion Independent chapels in Bristol, help us to place him in society locally and give us the touchstones of his interests: evangelism, Abolition, the 'Catholic Question', the Parliamentary redress of Dissenters' political grievances and the 'Prophetical Con¬ troversy'. Along with other artists, Colman used favourite genres of the era (the fairground picture, for example, and the biblical cataclysm) in order to present propaganda. But his unique approach to the use of art as a vehicle for dogma and political messages was his fusion of the emblem tradition with the visual formulae adopted by his contemporaries in the 'School of Catastrophe', especially in those paintings where he acknowledged the Sublime through his treatment, in poetic landscapes, of biblical epics and events from the Apocalypse.

Section C demonstrates the lyric qualities Colman obviously admired in the Psalms and in the hymns of English Dissent, particularly the hymnody of Isaac Watts. Finally, Section D shows that Samuel Colman found a consonant synthesis by being both sincere and optimistic in the presentation of his belief in the positive culmination of Salvation history.